Peran Komunitas Vespa Scoots. ID Palembang dalam Menjaga Solidaritas - Jefry, Arinaldo; Hasmawati, Fifi; Muslimin (Pubmedia Social Sciences and Humanities, 2024)
This research is entitled "The Role of the Vespa Scoots.id Palembang Community in Maintaining Solidarity". Vespa is a vehicle that has its own charm due to its distinctive shape and appearance. As the times progress and become more modern, the Vespa has become a vehicle that is quite popular, although the development of increasingly advanced transportation does not make the Vespa vehicle obsolete. This research aims to determine group communication in the Vespa Scoots.id Palembang Community in maintaining solidarity. The research uses descriptive qualitative methods with data collection techniques of observation, interviews and documentation. In this research, groupthink theory is used. The research results show that the communication between the Vespa Scoots.id Palembang Community group in maintaining solidarity is very high, this is because there is high cohesiveness in the community, there is a sense of family in solving problems, and there is complex decision making. Group communication in the Vespa Scoots.id Palembang community includes small group communication. The solidarity built by the Vespa Scoots.id Palembang Community is mechanical solidarity. Conclusion The Vespa Scoots.id Palembang community has very high solidarity and the group communication process built by the Vespa Scoots.id Palembang community in maintaining solidarity is that the chairman, administrators and members can communicate and can provide each other with ideas, opinions and input for the community.